2012
DOI: 10.1016/j.anr.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Placement: The Process of Decision Making and Adaptation among Adult Children Caregivers of Demented Parents in Korea

Abstract: The findings of the study provide the basic information for developing proactive strategies to support family caregivers better in the difficult period of nursing home placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 25 publications
4
66
0
Order By: Relevance
“…Carers report a shift in the dynamic to a "mother/child" type relationship and Table 4. Summary of triggers, barriers, and facilitators to decision-making (Butcher et al, 2001;Ducharme et al, 2012) Desire to honor person with dementia's wishes (Elliott et al, 2009) Family and professionals perspectives (Livingston et al, 2010;Ducharme et al, 2012) Carer unable to cope and care/ deterioration in carer health (Cohen et al, 1993;Caron et al, 2006;Ducharme et al, 2012) Emotional impact (anguish, burden guilt) (Butcher et al, 2001;Livingston et al, 2010) Support from others once decision made (Butcher et al, 2001) Change in living environment (Caron et al, 2006) Resistance from person with dementia (Livingston et al, 2010;Chrisp et al, 2012;Wolfs et al, 2012;Chrisp et al, 2013) Relationship to person with dementia (Wackerbarth, 1999) Person with dementia's ability to make decisions (Caron et al, 2006) Barriers to accessing services/lack of support/information (Wackerbarth, 1999;Butcher et al, 2001;Livingston et al, 2010) Adapting caring role following a decision (Kwon and Tae, 2012) Cultural treachery and distress (Chang and Schneider, 2010;Chang et al, 2011;Kwon and Tae, 2012) Collaborating with healthcare professionals (Walker and Dewar, 2001;Heinrich et al, 2003;Torke et al, 2013) Role change to "mother/child" (Cairns, 2012) Mild to moderate dementia severity (Smebye et al, 2012) Knowing when the "right" take to ...…”
Section: Role Transitions and Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carers report a shift in the dynamic to a "mother/child" type relationship and Table 4. Summary of triggers, barriers, and facilitators to decision-making (Butcher et al, 2001;Ducharme et al, 2012) Desire to honor person with dementia's wishes (Elliott et al, 2009) Family and professionals perspectives (Livingston et al, 2010;Ducharme et al, 2012) Carer unable to cope and care/ deterioration in carer health (Cohen et al, 1993;Caron et al, 2006;Ducharme et al, 2012) Emotional impact (anguish, burden guilt) (Butcher et al, 2001;Livingston et al, 2010) Support from others once decision made (Butcher et al, 2001) Change in living environment (Caron et al, 2006) Resistance from person with dementia (Livingston et al, 2010;Chrisp et al, 2012;Wolfs et al, 2012;Chrisp et al, 2013) Relationship to person with dementia (Wackerbarth, 1999) Person with dementia's ability to make decisions (Caron et al, 2006) Barriers to accessing services/lack of support/information (Wackerbarth, 1999;Butcher et al, 2001;Livingston et al, 2010) Adapting caring role following a decision (Kwon and Tae, 2012) Cultural treachery and distress (Chang and Schneider, 2010;Chang et al, 2011;Kwon and Tae, 2012) Collaborating with healthcare professionals (Walker and Dewar, 2001;Heinrich et al, 2003;Torke et al, 2013) Role change to "mother/child" (Cairns, 2012) Mild to moderate dementia severity (Smebye et al, 2012) Knowing when the "right" take to ...…”
Section: Role Transitions and Perceptionsmentioning
confidence: 99%
“…Carers reported emotional distress after the decision, which they sought to manage by adapting their caring role to visitor to the nursing home and seeking support for their decisions from others (Kwon and Tae, 2012).…”
Section: Whole Family Shared Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korean society has been traditionally greatly influenced by Confucianism, and adult children who fail to care for their parents tend to experience guilt and suffer hardships among their family members (Kwon & Tae, 2012). Finally, at the country level, the cost of caring for dementia patients escalates, which results in an increasing economic burden (Versijpt, 2014).…”
mentioning
confidence: 99%
“…After interviewed 30 caregivers of the elderly with dementia in Taiwan, Chang and Schneider (2010) found that there were four stages in the resettlement decision: 1) initiation of decision; 2) assessment of decision; 3) confirm of decision; and 4) evaluation of final decision [15]. Kwon & Tae (2012) did a research about the South Korean caregivers', and found that decision-making process mainly has four stages: 1) realizing a dead end; 2) seeking a way out; 3) accepting the inevitable decision; and 4) reorienting to change [16].…”
Section: Research Themementioning
confidence: 99%